Anti-inflammatory Activity of Essential Oil of Canarium Strictum Roxb: Anti-inflammatory activity of essential oil of Canarium strictum Roxb - Ragunathan Muthuswamy; Senthamarai R (Iranian Journal of Pharmaceutical Sciences, 2013)
Canarium L., used in folk medicine as anti-inflammatory, antibacterial, antifungal, antitumor and heptoprotective and antioxidant and anti diabetic. The present study investigated the in vivo anti-inflammatory activity of essential oil obtained by hydro distillation of Black dammer resin of Canarium strictum Roxb. Anti-inflammatory activity of essential oil of Canarium strictum Roxb., EOCS (10-100 mg/kg) has been established by using the carrageenan (acute inflammation model) and formalin (chronic inflammation model) induced paw edema in mice. The dose dependent activity has been observed at the higher dose of EOCS 100 mg /kg (P<0.0001). EOCS exhibited momentous anti-inflammatory activity that was compared with standard drug diclofenac sodium in acute inflammatory animal models. The perceived anti-inflammatory activity might be due to inhibition of histamine, serotonin, kinins, substance P and prostaglandins, and bradykinin at the inflamed area. On the other hand, in the formalin test EOCS 100 mg /kg reduced chronic inflammation most effectively (P<0.0001). Our data supported that EOCS capable to inhibit the paw edema in acute and chronic inflammation in the experimental animal models can be evident to use this oil for the treatment of chronic and acute inflammatory disorders. More elaborate investigation is needed in this aspect and to correlate the possible effect of major terpene which it produced anti-inflammatory activity.